From Tradition to Rationality: Understanding Voter Behavior in Madura’s Local Elections - Marijan, Kacung; Mardiyanta, Antun; Holilah, Holilah (UIN Sunan Ampel Surabaya, 2024)
This study offers an in-depth comparative analysis of the voting behavior of the Madurese community in regional head elections, focusing on the differences between traditional voters influenced by kiai (Islamic scholars) and voters who tend to consider rational factors. This case study examines three main groups: the santri (religious students), the educated class, and the general public. The research is rooted in the central role of kiai within Madura's social and political structure, which has traditionally influenced election outcomes. However, recent corruption cases involving kiai who have served as regional heads raise questions about whether their influence remains or if there has been a shift in the community's voting behavior. The research employs a qualitative approach with a case study design, conducted in four regencies: Bangkalan, Sampang, Pamekasan, and Sumenep. Data were gathered through participatory observation, in-depth interviews with key informants from the three community groups, and documentation studies. Informants were selected based on their cultural involvement and experience in the election process. The findings indicate that although kiai continue to wield significant influence, especially among the santri, there is an emerging trend toward more rational voting behavior among the educated class and the general public. Factors such as candidate quality, vision and mission, and proposed programs are increasingly considered, particularly by students. Additionally, corruption cases involving kiai have led to more critical public perceptions of kiai in politics. This study identifies four voter typologies in Madura: rational, critical, traditional, and skeptical, highlighting the complexity of voting behavior in the region